Dual JAK2/Aurora kinase A inhibition prevents human skin graft rejection by allo‐inactivation and ILC2‐mediated tissue repair. Issue 3 (8th November 2021) - Walton, Kelly; Walker, Kirsti; Riddle, Megan; Koehn, Brent H.; Reff, Jordan; Sagatys, Elizabeth M.; Linden, Michael A.; Pidala, Joseph; Kim, Jongphil; Lee, Marie C.; Kiluk, John V.; Hui, Jane Yuet Ching; et al.
Abstract : Prevention of allograft rejection often requires lifelong immune suppression, risking broad impairment of host immunity. Nonselective inhibition of host T cell function increases recipient risk of opportunistic infections and secondary malignancies. Here we demonstrate that AJI‐100, a dual inhibitor of JAK2 and Aurora kinase A, ameliorates skin graft rejection by human T cells and provides durable allo‐inactivation. AJI‐100 significantly reduces the frequency of skin‐homing CLA + donor T cells, limiting allograft invasion and tissue destruction by T effectors. AJI‐100 also suppresses pathogenic Th1 and Th17 cells in the spleen yet spares beneficial regulatory T cells. We show dual JAK2/Aurora kinase A blockade enhances human type 2 innate lymphoid cell (ILC2) responses, which are capable of tissue repair. ILC2 differentiation mediated by GATA3 requires STAT5 phosphorylation (pSTAT5) but is opposed by STAT3. Further, we demonstrate that Aurora kinase A activation correlates with low pSTAT5 in ILC2s. Importantly, AJI‐100 maintains pSTAT5 levels in ILC2s by blocking Aurora kinase A and reduces interference by STAT3. Therefore, combined JAK2/Aurora kinase A inhibition is an innovative strategy to merge immune suppression with tissue repair after transplantation. Abstract : Targeting JAK2 and Aurora kinase A with a small molecule inhibitor aligns selective immune suppression and tissue repair after transplantation by supporting human regulatory T cells and type 2 innate lymphoid cells.